Analisis Pelaksanaan Pencatatan Petty Cash (Kas Kecil) Pada PT MNI Entertainment Jakarta Pusat - Eulin Karlina; Fajri Ariandi; Siti Dedeh Humaeroh; Rini Martiwi (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
Each company must have a cash section formed, and the cash portion will be assisted by a petty cash section signed by the petty cash implementation officer and related functions to assist operational performance directly. transactions that occur are not very complicated, but must carry out management properly and thoroughly based on the operating procedures of the existing company. For this reason, the author tries to make a final assignment regarding the recording of petty cash at PT MNI Entertainment, Central Jakarta. The method used in this study is to use a qualitative descriptive method with data collection techniques through observation, interviews and documentation. The registration of petty cash at PT MNI Entertainment Central Jakarta is by using the imperst method, which in this method the determination of the amount of petty cash funds is always fixed in the period. In the implementation of the Petty Cash there are implementation procedures and several records that are applied to carry out operational activities such as the establishment of a petty cash fund, and refill petty cash funds.